New Treatment for Phenylketonuria - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1990)
Sixteen adolescents and young adults with phenylketonuria were treated with a mixture of valine, isoleucine, and leucine for four 3-month periods, and biochemical and neuropsychological tests were carried out before and after treatment at the Metabolic Disease Center, Children's Hospital Medical Center, University of Cincinnati College of Medicine.